Studies on Suitability of Grasses for Protection of Field-earthen-structures in Agra Region of Yamuna Ravines - Prajapati, M. C.; Phadke, A. B.; Agarwal, M. C. (Indian Forester, 1973)
An experiment to select suitable grass species for protection of the bunds of newly formed terraces in Jamuna ravines, was conducted at Research Station, Chhalesar (Agra) from 1960 to 1964. Of the eleven grass species studied, Cynodon dactylon (L.) Pers. with statistically significant supreme root and shoot characteristics afforded excellent protection to the terrace bunds against water erosion. This was followed by Dichanthium annulatum (Forsk) Stapf., Panicum antidotale Retz., Panicum repens Linn., Cenehrus ciliaris Linn., Panicum maximum Jacq., Brachiaria brizantha (Hochst) Stapf., Chrysopogon fulvus (Spreng) Chiov., Pennisetum purpureum Schum., Cynodon plectostanchyus (K.Schum) Pilger., and Brachiaria mutica (Forsk) Stapf., in order of merit. Pennisetum purpureum Schum., recorded highest yield per hectare as well as the highest preference in palatability test. The rat-damage as minimum to those bunds which were protected with Cynodon dactylon (L.) Pers.